Análisis del liderazgo institucional y su incidencia en el compromiso de los servidores públicos del GAD del cantón Bolívar período 2019-2021 - Cedeño Mejía, Carlos Yimmy (2021)
Leadership is considered from the beginning of time as that ability or skill that a person must influence, lead and direct others. On the other hand, there is the institutional commitment, which is considered as a set of attitudes that employees or servants have in the performance of their activities, this is how the commitment and good work performance of these depends in some way on the manner in which leadership is exercised. Based on the aforementioned, the objective of this research is to analyze institutional leadership and its impact on the commitment of public servants of the Municipal GAD of Bolívar canton in the period 2019-2021, for the improvement of work performance. To fulfill the purpose of this research, it was necessary to apply the inductive, deductive, analytical synthetic and correlational method and the bibliographic, field and descriptive research techniques were used, several data collection instruments were also applied, such as the survey applied to public servants of the GAD, an interview to the city mayor, the multifactorial leadership questionnaire MLQ carried out to the cantonal authorities and the questionnaire of institutional commitment applied to public servants, with this information the data was known firsthand and facts required in the investigation, in order to carry out an examination of the different strategies that can be attached to the process and, through an improvement plan, propose possible solutions to the posed problem.